TOP-200 Higher Education Institutions in Four International Ratings: Comparative Analysis - Ivan E. Zadorozhnyuk; Larisa Yu. Korosteleva; Boris K. Tebiyev (Высшее образование в России)
Rating places of 200 higher education institutions according to ARWU, THE, QS and Moscow International Rating (MosIR) are compared. The authors give an interpretation of a phenomenon of domination of English-language higher education institutions on the top positions and as well as higher education institutions of Europe and North America. The paper dwells on the main ranking parameters in Moscow International University Ranking (MosIR) and its innovative charac teristics, in particular the new parameter “University and Society”. The ranking “Three University Missions” focuses on the social openness of higher education institutions, their communications with society. Special attention is paid to the ranking paradoxes. The authors come to a conclusion that the introduction of Moscow International University Ranking improves the competitive environment in the global educational space.